The Influence of Digital Culture on the Development of Students' Linguistic Identity - Irianto, Sugeng; Malik, Fatima (Yayasan Pendidikan Islam Daarut Thufulah, 2025)
Background. This research is motivated by significant changes in the way students interact and communicate due to the development of digital culture. In the midst of the rapid use of social media and other digital platforms, its influence on the development of students' linguistic identities has not been widely researched. Digital culture has created a new communication space that tends to be informal and different from the language norms in the academic space. Purpose. This study aims to analyze how digital culture affects the development of students' linguistic identities in the context of education. Method. This study uses a quantitative approach with a descriptive design. Data was collected through questionnaires and interviews involving 200 students from several high schools. The research instrument is designed to uncover the pattern of students' language use in the digital world and its relation to formal language skills. Results. The results showed that most students use informal language, such as slang and slang, more often in cyberspace. This difference causes some students to have difficulty adapting to the formal language used in academic contexts. Although some students have successfully adjusted, there are indications that these changes have impacted the effectiveness of their formal language use. Conclusion. Digital culture affects students' linguistic identities in a complex way. Therefore, a more flexible approach to education is needed to deal with these challenges. Advanced research can explore other factors that influence the development of students' linguistic identities, such as family factors and local culture.